Twitter: High on celebrity gossip, low on news discussion - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
Twitter is regarded as a highly popular platform for online communications. It was said to have played a role in facilitating – 140 characters at a time – social movements that supported key events such as the Arab Spring. And because Twitter messages (or 'tweets' as they are called) are compact and quickly transmitted, they are widely used to spread and share breaking news, personal updates and spontaneous ideas.